Prawne implikacje wybranych elementów terminu „wojna hybrydowa” - Ochmann, Paweł (Wydawnictwo Naukowe UAM, 2019)
The term ‘hybrid war’ is not a legal term. It belongs to the terminology and concepts used in the studies on international relationships. Due to its popularization in mass media it has recently started to be used in new contexts. The purpose of the article is to ascertain the precise meaning of the term, and to determine the legal implications which a particular understanding of it may have in international public law. Certain understandings or interpretations of a given term determine its legal consequences and allow the assessment of their implications from the point of view of international law. Therefore in the first part of the article, a review and an examination of different ways of understanding the term ‘hybrid war’ have been conducted. Although the definitions that had been analyzed are noteworthy and they emphasize some aspects of the ‘hybrid war,’ they lack a definition of the term that would take into consideration all the dimensions of the issue of a hybrid war. Thus the attempt taken by the author to propose his own definition, aggregating all observations and insights made by the international relations experts so far, and enumerating the distinctive characteristics of hybrid wars. After that, some typical elements of a hybrid war are analyzed from the point of view of international public law. The paper investigates the possibility of qualifying hybrid methods as the ‘use of force,’ an ‘aggression’ and an ‘armed attack’ within the meaning of the United Nations Charter. It also examines the admissibility of a counter-attack within the framework of the right to self- defence. The issue raises many doubts particularly with regard to activities from below the threshold of war that are distinctive characteristics of a hybrid war. The legal implications of the use of a non-state actor to conduct an armed activity under international law were also raised, being referred to as proxy war.
Legal implications of selected elements of the term ‘hybrid war’
Keywords: hybrid war; military conflict; international law